Reification and the Dandy: Beppo, Byron, and other Queer Things - George, Laura (Romanticism on the Net, 2004)
AbstractWhen contemporary critics like McGann and Christensen link the figure of the dandy with the category of “the thing,” they participate in a rich and enduring cultural pattern that dates back at least to the Restoration. “Reification and the Dandy” elaborates this cultural history through an examination of eighteenth-century British rhetorics of foppishness and their reliance on the category of the thing in order to situate its contemporary iterations in their historical context. Recalling this history also underscores the extent to which Byron’s poetics in Beppo are disarmingly queer in their performance of a refusal to feel the degradation of foppishness, thinghood, and impotent triviality. Beppo neither resolves nor exorcises the double binds and blinds of poetic composition in a reified culture, but it performs those binds for us in a slight work, next of kin to a nonentity. In Beppo Byron offers foppery as poetics itself, making the slight, the trivial, the barely there, turn his career. The ottava rima may have been inspired by Frere and Pulce, but the foppish poem, itself a dandiacal confrontation with Wordsworthian poetics, was Byron’s own.